2021
DOI: 10.1002/pssb.202100025
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Local Lattice Distortion on Elastic Properties of Hexagonal Close‐Packed TiZrHf and TiZrHfSc Refractory Alloys

Abstract: The unique mechanical properties and local lattice distortion (LLD) for hexagonal close‐packed (HCP) multiple principal element alloys (MPEAs) are very rarely studied so far. Employing density functional theory calculation based on special quasirandom structure, this work studies the influences of LLD on elastic properties for both novel hexagonal TiZrHf(Sc) MPEAs. Compared to the pristine structures, the lattice stability of distorted random structures is improved evidently. Moreover, LLD obviously lessens th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 44 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…Previous studies have suggested that the local lattice distortions in a material can also affect the elastic isotropy/anisotropy. In particular, higher local lattice distortions have been shown to correlate with increased elastic isotropy 72 , large microscale residual stresses can also influence lattice distortions 73 . As previously mentioned, laser-based AM techniques result in extremely high cooling rates which can induce significant thermal residual stresses.…”
Section: Machine Learning Analysis and Theoretical Elastic Constantsmentioning
confidence: 99%
“…Previous studies have suggested that the local lattice distortions in a material can also affect the elastic isotropy/anisotropy. In particular, higher local lattice distortions have been shown to correlate with increased elastic isotropy 72 , large microscale residual stresses can also influence lattice distortions 73 . As previously mentioned, laser-based AM techniques result in extremely high cooling rates which can induce significant thermal residual stresses.…”
Section: Machine Learning Analysis and Theoretical Elastic Constantsmentioning
confidence: 99%
“…The equivalent plastic strain rate can be expressed as [37] ε p equ 0 ¼ ε 0 σ e σ flow m 0 (24) where σ flow is the flow stress and m ij ¼ 20 is the rate-sensitivity exponent.…”
Section: Dislocation Strengtheningmentioning
confidence: 99%
“…However, the quantitative prediction of mechanical properties in the dual-phase metastable HEAs has not yet been established due to the lack of the strengthening model. [22][23][24][25][26][27][28][29][30] To solve this critical issue, we develop a physically based constitutive model to quantitatively evaluate the contribution of various strengthening mechanisms to strength during deformation, considering the effect of lattice distortion, dislocation, grain boundary, and phase interface. The current model can capture accurately the flow stress, which can be used as a helpful tool to predict the mechanical properties of the metastable HEAs.…”
Section: Introductionmentioning
confidence: 99%